Catalyst for removing hydrocarbon impurities from carbon dioxide and preparation method thereof

By supporting precious metal particles such as platinum and palladium on the composite support particles, the alumina, silicon oxide, and magnesium oxide composite aerogel support prepared by the sol-gel method significantly improves the performance of the catalyst, solves the problems of low activity and short service life of the existing catalysts, and achieves efficient removal of hydrocarbon impurities in carbon dioxide.

CN119608156APending Publication Date: 2025-03-14QINGDAO NEW CHEM
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411598257.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Existing catalysts have low activity, poor mechanical properties, low removal efficiency and short service life when removing hydrocarbon impurities from carbon dioxide, especially under high temperature conditions.

Method used

By loading the active components (such as platinum and palladium) on the composite support particles, the composite support particles are supported on alumina, silica, magnesium oxide composite aerogel prepared by sol-gel method and obtained by grinding and sieving.

Benefits of technology

It significantly improves the activity, mechanical properties and removal efficiency of the catalyst, while extending the service life, and maintains excellent catalytic performance especially under high temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005127533510000091
    Figure BDA0005127533510000091
  • Figure BDA0005127533510000101
    Figure BDA0005127533510000101
Patent Text Reader

Abstract

The invention relates to the technical field of carbon dioxide dealkylation, and discloses a catalyst for removing hydrocarbon impurities in carbon dioxide and a preparation method of the catalyst. According to the catalyst for removing hydrocarbon impurities from carbon dioxide, active components are loaded on composite carrier particles; the composite carrier particles are obtained by loading a catalytic promoter cerium oxide on composite aerogel, grinding and sieving; the composite aerogel is prepared from a coagulant aid and at least two aerogel precursors by a sol-gel method. The preparation method of the catalyst for removing hydrocarbon impurities in carbon dioxide comprises the following preparation steps: 1) preparing composite aerogel from an aerogel precursor and a coagulant aid through a sol-gel method; 2) soaking the composite aerogel in a cerium nitrate solution, naturally airing, drying, roasting, grinding and sieving to obtain composite carrier particles; and 3) dipping the composite carrier particles in a mixed solution of active components, standing, drying and roasting to obtain the catalyst for removing hydrocarbon impurities from carbon dioxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a catalyst for removing hydrocarbon impurities from carbon dioxide and a preparation method thereof. Background Art

[0002] With the increasing concern about the impact on the environment during industrial production, the efficient removal of hydrocarbon impurities in carbon dioxide has become an important task. The presence of hydrocarbon impurities not only affects the purity of the carbon dioxide product, but may also cause corrosion or blockage to the equipment in the subsequent use process, thereby affecting the safety and economy of the entire process. Therefore, it is particularly important to develop efficient catalysts for the removal of hydrocarbon impurities in carbon dioxide.

[0003] However, existing catalysts face many challenges in practical applications, including but not limited to low activity, poor mechanical properties, low removal efficiency and short service life. These problems limit the widespread application of catalysts in industry, especially when running for a long time under high temperature conditions. In order to overcome these shortcomings, researchers have been committed to improving the performance of catalysts through different approaches in recent years, such as optimizing catalyst components, improving preparation technology and improving reaction conditions.

[0004] The present invention proposes a catalyst for removing hydrocarbon impurities from carbon dioxide and a preparation method thereof, aiming to significantly improve the activity and mechanical properties of the catalyst by compositely modifying the carrier and carrying precious metal particle materials such as platinum (Pt) and palladium (Pd), while ensuring high dehydrogenation efficiency and extending service life. Summary of the invention

[0005] The purpose of the present invention is to provide a catalyst for removing hydrocarbon impurities from carbon dioxide and a preparation method thereof, so as to solve the technical problems mentioned in the above background technology.

[0006] The technical solution for achieving the purpose of the present invention is:

[0007] A catalyst for removing hydrocarbon impurities from carbon dioxide, wherein the catalyst for removing hydrocarbon impurities from carbon dioxide is prepared by loading active components on composite carrier particles; the composite carrier particles are prepared by loading a catalyst promoter, cerium oxide, on a composite aerogel through grinding and sieving; the composite aerogel is prepared by using a sol-gel method to prepare a coagulant and at least two aerogel precursors.

[0008] Furthermore, the active components are palladium and platinum.

[0009] Furthermore, the coagulant aid is 1,2-propylene oxide or polyvinyl pyrrolidone.

[0010] Furthermore, the aerogel precursor is aluminum chloride hexahydrate, tetraethyl orthosilicate and magnesium chloride hexahydrate.

[0011] The present invention also provides a method for preparing a catalyst for removing hydrocarbon impurities from carbon dioxide, comprising the following preparation steps:

[0012] (1) preparing a composite aerogel by a sol-gel method using an aerogel precursor and a coagulant;

[0013] (2) soaking the composite aerogel in a cerium nitrate solution, drying it naturally, calcining it, grinding it, and sieving it to obtain composite carrier particles;

[0014] (3) The composite carrier particles are immersed in a mixed solution of active components, left to stand, dried, and calcined to obtain a catalyst for removing hydrocarbon impurities from carbon dioxide.

[0015] Furthermore, the aerogel precursor uses aluminum chloride hexahydrate, tetraethyl orthosilicate and magnesium chloride hexahydrate, and the mass fractions of aluminum chloride hexahydrate, tetraethyl orthosilicate and magnesium chloride hexahydrate are 2-2.4 mass parts, 0.94 mass parts and 3.5-3.9 mass parts respectively.

[0016] Furthermore, the coagulant aid is polyvinyl pyrrolidone, and the mass fraction of polyvinyl pyrrolidone is 5.4 to 5.6 mass parts.

[0017] Furthermore, the CeO2 loading of the composite carrier particles is 8-10%.

[0018] Furthermore, the loading amount of the active component of the catalyst for removing hydrocarbon impurities from carbon dioxide is 0.45%.

[0019] Furthermore, the active components are palladium and platinum, and the loading amounts of palladium and platinum on the catalyst for removing hydrocarbon impurities in carbon dioxide are 0.28-0.32% and 0.13-0.17% respectively.

[0020] By adopting the above technical solution, the present invention has the following beneficial effects:

[0021] (1) The catalyst for removing hydrocarbon impurities from carbon dioxide of the present invention is first prepared by a sol-gel method from aluminum chloride hexahydrate, tetraethyl orthosilicate, and magnesium chloride hexahydrate to obtain a composite aerogel, then cerium oxide is loaded on the composite aerogel, and then composite carrier particles are obtained by grinding and sieving, and finally platinum and palladium are loaded on the composite carrier particles. The catalyst for removing hydrocarbon impurities from carbon dioxide prepared by the present invention has high activity, good mechanical properties, high removal efficiency, and long service life.

[0022] (2) The catalyst for removing hydrocarbon impurities from carbon dioxide of the present invention adopts a sol-gel method to prepare aluminum chloride hexahydrate, tetraethyl orthosilicate, and magnesium chloride hexahydrate to obtain a composite aerogel of aluminum oxide, silicon oxide, and magnesium oxide; wherein aluminum oxide has a high specific surface area and a rich pore structure, can provide a large number of active sites, and is conducive to the dispersion and adsorption of active components. The acidic and basic sites on its surface can adjust the acid-base properties of the catalyst, which helps to improve the selectivity and activity of the catalyst. In addition, aluminum oxide has good thermal stability and can maintain structural integrity under high temperature conditions to prevent sintering and deactivation of the catalyst; silicon oxide also has a high specific surface area and a rich pore structure, which can provide more adsorption sites and diffusion paths, which is conducive to the dispersion of active components and the transmission of reactants. Its high mechanical strength enhances the physical stability of the composite aerogel and prevents breakage and pulverization during use. The hydrophobicity of the silicon oxide surface can reduce the adsorption of water molecules and prevent catalyst poisoning and deactivation; magnesium oxide is a strong alkaline substance that can neutralize the acidic sites on the catalyst surface, adjust the acid-base balance of the catalyst, and help to improve the selectivity and activity of the catalyst. activity; magnesium oxide has good thermal stability and can maintain structural integrity under high temperature conditions to prevent sintering and deactivation of the catalyst; magnesium oxide can provide a certain oxygen storage capacity, which helps to maintain the active oxygen species on the catalyst surface and improve the catalytic activity; through the co-existence of alumina and magnesium oxide, the acid-base properties of the composite aerogel can be adjusted, providing a suitable acid-base environment, which is conducive to the dispersion of active components and the catalytic reaction; at the same time, the high specific surface area and rich pore structure of alumina and silicon oxide provide a large number of active sites and diffusion paths, which promote the dispersion of active components and the transmission of reactants; the combined action of alumina and magnesium oxide significantly improves the thermal stability of the composite aerogel and prevents sintering and deactivation under high temperature conditions; in addition, the alkaline nature of magnesium oxide neutralizes the acid sites on the catalyst surface, reduces the agglomeration tendency of metal particles, and maintains the high dispersibility and stability of the catalyst; through the synergistic effect of these components, the composite aerogel carrier not only has a high specific surface area, rich pore structure and good thermal stability and mechanical properties, but also can provide a suitable acid-base environment and oxygen storage capacity, thereby significantly improving the overall performance of the catalyst.

[0023] (3) The present invention loads cerium oxide on the composite aerogel, further enhancing the performance of the catalyst; wherein, cerium oxide has good oxygen storage capacity, can activate oxygen molecules at low temperatures, and promote the oxidation reaction of hydrocarbon substances. The reversible conversion between tetravalent cerium ions and trivalent cerium ions provides high oxygen mobility, helps to maintain active oxygen species on the catalyst surface, and improves catalytic activity; the presence of cerium oxide also helps to disperse precious metal particles platinum and palladium, reduce their tendency to agglomerate, thereby maintaining high catalytic activity and stability; in addition, cerium oxide has good thermal stability, can maintain structural integrity under high temperature conditions, and further enhance the thermal stability of the composite aerogel; the high specific surface area and pore structure of the composite aerogel provide more contact surfaces for cerium oxide, enhance its oxygen storage capacity and oxygen mobility, and enable the catalyst to maintain efficient oxidation activity under low temperature conditions; the presence of cerium oxide helps to disperse precious metal particles (such as platinum and palladium), reduce their tendency to agglomerate, and maintain high dispersion and stability of the catalyst, Ce 4+ and Ce 3+ The reversible transformation between them also helps to maintain the dispersion state of the metal particles; the high specific surface area and rich pore structure of the composite aerogel provide more dispersion sites for the precious metal particles, further enhancing the dispersion effect. At the same time, its high mechanical strength and thermal stability also prevent the sintering of the metal particles and extend the service life of the catalyst; both the composite aerogel and cerium oxide have good thermal stability and can maintain structural integrity under high temperature conditions. The cerium oxide loaded on the composite aerogel further enhances the thermal stability of the composite aerogel, so that the catalyst can still maintain excellent catalytic performance under high temperature conditions; this synergistic effect enables the catalyst to exhibit high activity, good mechanical properties and thermal stability, as well as excellent removal efficiency and a long service life in the process of removing hydrocarbon impurities from carbon dioxide.

[0024] (4) The coagulant aid of the present invention adopts polyvinyl pyrrolidone, and a composite aerogel with a mesoporous structure is prepared by a sol-gel method; the addition of PVP not only regulates the gelation process and forms a uniform and stable mesoporous structure, but also significantly increases the specific surface area and porosity of the composite aerogel; this mesoporous structure provides a large number of active sites and diffusion paths, which is beneficial to the dispersion of active components and the transmission of reactants, thereby improving the overall activity and catalytic efficiency of the catalyst; at the same time, the mesoporous structure also enhances the mechanical strength and thermal stability of the composite aerogel, so that it can still maintain the integrity of the structure under high temperature conditions, thereby extending the service life of the catalyst. DETAILED DESCRIPTION

[0025] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with specific implementation methods.

[0026] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.

[0027] The following embodiments are only used to more clearly illustrate the technical solutions of the present invention, and are not intended to limit the protection scope of the present invention.

[0028] Example 1

[0029] A method for preparing a catalyst for removing hydrocarbon impurities from carbon dioxide comprises the following preparation steps:

[0030] (1) 2 parts by mass of aluminum chlorohexahydrate, 0.94 parts by mass of tetraethyl orthosilicate, and 3.5 parts by mass of magnesium chlorohexahydrate are added to a mixed solvent of 17 parts by mass of deionized water and ethanol, and stirred at 200 rpm until the aluminum chlorohexahydrate, tetraethyl orthosilicate, and magnesium chlorohexahydrate are completely dissolved, and stirring is continued for 23 hours to fully hydrolyze the aluminum chlorohexahydrate, tetraethyl orthosilicate, and magnesium chlorohexahydrate to obtain a mixed solution; wherein the volume ratio of deionized water to ethanol in the mixed solvent of deionized water and ethanol is 1:1; 5.4 parts by mass of polyvinyl pyrrolidone as a coagulant aid is taken and stirred at 200 rpm. The mixture was added dropwise to the mixed solution, and stirring was continued for 14 minutes. The mixture was then transferred to a mold and allowed to stand until a wet gel was formed. The mixture was then aged for 24 hours. The excess water in the wet gel was replaced with anhydrous ethanol at 40°C, and the ethanol was replaced every 12 hours for 7 days. The replaced gel was placed in a supercritical drying kettle, and the oxygen in the kettle was replaced with nitrogen. The pressure in the kettle was raised to 2.4 MPa, and the temperature was raised to 264°C. At the same time, the pressure in the kettle was controlled to 7.4 MPa, and the pressure was kept constant. After the temperature was kept constant for 1.4 hours, the pressure was slowly released to normal pressure, and finally the temperature was lowered to room temperature to obtain a composite aerogel.

[0031] (2) The composite aerogel was immersed in an equal volume of cerium nitrate solution for 1.8 hours, dried naturally and then dried overnight, then heated to 500°C at a heating rate of 4°C / min, calcined for 3.5 hours, ground and sieved to obtain composite carrier particles with a particle size of 2 mm, wherein the CeO2 loading in the composite carrier particles was 8%;

[0032] (3) The composite carrier particles were immersed in a mixed solution of equal volumes of chloroplatinic acid hexahydrate and palladium chloride, left at room temperature for 12 h, then dried at 120°C for 5.5 h, then heated to 450°C at 4°C / min, and calcined for 2.5 h to obtain a catalyst for removing hydrocarbon impurities from carbon dioxide; wherein the loading amounts of platinum and palladium were 0.13% and 0.32%, respectively.

[0033] Example 2

[0034] A method for preparing a catalyst for removing hydrocarbon impurities from carbon dioxide comprises the following preparation steps:

[0035] (1) 2.2 parts by mass of aluminum chlorohydrate, 0.94 parts by mass of tetraethyl orthosilicate, and 3.7 parts by mass of magnesium chlorohydrate are added to a mixed solvent of 18 parts by mass of deionized water and ethanol, and stirred at 300 rpm until the aluminum chlorohydrate, tetraethyl orthosilicate, and magnesium chlorohydrate are completely dissolved, and stirring is continued for 24 hours to fully hydrolyze the aluminum chlorohydrate, tetraethyl orthosilicate, and magnesium chlorohydrate to obtain a mixed solution; wherein the volume ratio of deionized water to ethanol in the mixed solvent of deionized water and ethanol is 1:1; 5.5 parts by mass of polyvinyl pyrrolidone, a coagulant aid, are taken and stirred at 300 rpm. The mixture was added dropwise to the mixed solution under the condition of 1% mol / l and stirred for 15 min. The mixture was then transferred to a mold and allowed to stand until a wet gel was formed. The mixture was then aged for 24 h. The excess water in the wet gel was replaced with anhydrous ethanol at 40 °C. The ethanol was replaced every 12 h for 7 days. The replaced gel was placed in a supercritical drying kettle. The oxygen in the kettle was replaced with nitrogen. The pressure in the kettle was raised to 2.5 MPa. The temperature was raised to 265 °C. The pressure in the kettle was controlled to 7.5 MPa. The pressure was kept constant. After the temperature was kept constant for 1.5 h, the pressure was slowly released to normal pressure. Finally, the temperature was lowered to room temperature to obtain a composite aerogel.

[0036] (2) The composite aerogel was immersed in an equal volume of cerium nitrate solution for 2 hours, dried naturally and then dried overnight, then heated to 550°C at a heating rate of 5°C / min, calcined for 4 hours, ground and sieved to obtain composite carrier particles with a particle size of 3 mm, wherein the CeO2 loading in the composite carrier particles was 9%;

[0037] (3) The composite carrier particles were immersed in a mixed solution of equal volumes of chloroplatinic acid hexahydrate and palladium chloride, left at room temperature for 12 hours, then dried at 120°C for 6 hours, and then heated to 450°C at 5°C / min and calcined for 3 hours to obtain a catalyst for removing hydrocarbon impurities from carbon dioxide; wherein the loading amounts of platinum and palladium were 0.15% and 0.3%, respectively.

[0038] Example 3

[0039] A method for preparing a catalyst for removing hydrocarbon impurities from carbon dioxide comprises the following preparation steps:

[0040] (1) 2.4 parts by mass of aluminum chlorohydrate, 0.94 parts by mass of tetraethyl orthosilicate, and 3.9 parts by mass of magnesium chlorohydrate are added to a mixed solvent of 19 parts by mass of deionized water and ethanol, and stirred at 400 rpm until the aluminum chlorohydrate, tetraethyl orthosilicate, and magnesium chlorohydrate are completely dissolved, and stirring is continued for 25 hours to fully hydrolyze the aluminum chlorohydrate, tetraethyl orthosilicate, and magnesium chlorohydrate to obtain a mixed solution; wherein the volume ratio of deionized water to ethanol in the mixed solvent of deionized water and ethanol is 1:1; 5.6 parts by mass of polyvinyl pyrrolidone, a coagulant aid, are taken and stirred at 400 rpm. The mixture was added dropwise to the mixed solution under the condition of 40 ° C., and stirring was continued for 16 minutes. Then, the mixture was transferred to a mold and allowed to stand until a wet gel was formed. Then, the mixture was aged for 24 hours. After that, the excess water in the wet gel was replaced with anhydrous ethanol at 40 ° C. The ethanol was replaced every 12 hours for 7 days. The replaced gel was placed in a supercritical drying kettle, and the oxygen in the kettle was replaced with nitrogen. The pressure in the kettle was raised to 2.6 MPa, and the temperature was raised to 266 ° C. At the same time, the pressure in the kettle was controlled to 7.6 MPa, and the pressure was kept constant. After the temperature was kept constant for 1.6 hours, the pressure was slowly released to normal pressure, and finally the temperature was lowered to room temperature to obtain a composite aerogel.

[0041] (2) The composite aerogel was immersed in an equal volume of cerium nitrate solution for 2.2 hours, dried naturally and then dried overnight, then heated to 600°C at a heating rate of 6°C / min, calcined for 4.5 hours, ground and sieved to obtain composite carrier particles with a particle size of 4 mm, wherein the CeO2 loading in the composite carrier particles was 10%;

[0042] (3) The composite carrier particles were immersed in a mixed solution of equal volumes of chloroplatinic acid hexahydrate and palladium chloride, left at room temperature for 12 h, then dried at 120°C for 6.5 h, then heated to 450°C at 6°C / min, and calcined for 3.5 h to obtain a catalyst for removing hydrocarbon impurities from carbon dioxide; wherein the loading amounts of platinum and palladium were 0.17% and 0.28%, respectively.

[0043] Example 4

[0044] A method for preparing a catalyst for removing hydrocarbon impurities from carbon dioxide comprises the following preparation steps:

[0045] (1) 2.2 parts by mass of aluminum chlorohydrate, 0.94 parts by mass of tetraethyl orthosilicate, and 3.7 parts by mass of magnesium chlorohydrate are added to a mixed solvent of 18 parts by mass of deionized water and ethanol, and stirred at 300 rpm until the aluminum chlorohydrate, tetraethyl orthosilicate, and magnesium chlorohydrate are completely dissolved, and stirring is continued for 24 hours to fully hydrolyze the aluminum chlorohydrate, tetraethyl orthosilicate, and magnesium chlorohydrate to obtain a mixed solution; wherein the volume ratio of deionized water to ethanol in the mixed solvent of deionized water and ethanol is 1:1; 4.2 parts by mass of 1,2-propylene oxide, a coagulant aid, is taken and stirred at 300 rpm. The mixture was added dropwise to the mixed solution under the condition of 1% mol / l and stirred for 15 min. The mixture was then transferred to a mold and allowed to stand until a wet gel was formed. The mixture was then aged for 24 h. The excess water in the wet gel was replaced with anhydrous ethanol at 40 °C. The ethanol was replaced every 12 h for 7 days. The replaced gel was placed in a supercritical drying kettle. The oxygen in the kettle was replaced with nitrogen. The pressure in the kettle was raised to 2.5 MPa. The temperature was raised to 265 °C. The pressure in the kettle was controlled to 7.5 MPa. The pressure was kept constant. After the temperature was kept constant for 1.5 h, the pressure was slowly released to normal pressure. Finally, the temperature was lowered to room temperature to obtain a composite aerogel.

[0046] (2) The composite aerogel was immersed in an equal volume of cerium nitrate solution for 2 hours, dried naturally and then dried overnight, then heated to 550°C at a heating rate of 5°C / min, calcined for 4 hours, ground and sieved to obtain composite carrier particles with a particle size of 3 mm, wherein the CeO2 loading in the composite carrier particles was 9%;

[0047] (3) The composite carrier particles were immersed in a mixed solution of equal volumes of chloroplatinic acid hexahydrate and palladium chloride, left at room temperature for 12 hours, then dried at 120°C for 6 hours, and then heated to 450°C at 5°C / min and calcined for 3 hours to obtain a catalyst for removing hydrocarbon impurities from carbon dioxide; wherein the loading amounts of platinum and palladium were 0.15% and 0.3%, respectively.

[0048] Comparative Example 1

[0049] A method for preparing a catalyst for removing hydrocarbon impurities from carbon dioxide comprises the following preparation steps:

[0050] (1) 7.7 parts by weight of aluminum chlorohydrate was added to a mixed solvent of 18 parts by weight of deionized water and ethanol, and stirred at 300 rpm until aluminum chlorohydrate, ethyl orthosilicate, and magnesium chlorohydrate were completely dissolved, and the stirring was continued for 24 hours to fully hydrolyze aluminum chlorohydrate, ethyl orthosilicate, and magnesium chlorohydrate to obtain a mixed solution; wherein the volume ratio of deionized water to ethanol in the mixed solvent of deionized water and ethanol was 1:1; 5.5 parts by weight of polyvinyl pyrrolidone as a coagulant aid was added dropwise to the mixed solution under stirring at 300 rpm, and the mixture was continued. Stir for 15 minutes, then transfer to a mold and let stand until a wet gel is formed, then age for 24 hours, then replace the excess water in the wet gel with 40°C anhydrous ethanol, and replace the ethanol every 12 hours for 7 days; place the replaced gel in a supercritical drying kettle, replace the oxygen in the kettle with nitrogen, and raise the pressure in the kettle to 2.5MPa, raise the temperature to 265°C, and control the pressure in the kettle to 7.5MPa at the same time, keep the pressure constant, keep the temperature constant for 1.5 hours, slowly release the pressure to normal pressure, and finally wait for the temperature to drop to room temperature to obtain a composite aerogel;

[0051] (2) The composite aerogel was immersed in an equal volume of cerium nitrate solution for 2 hours, dried naturally and then dried overnight, then heated to 550°C at a heating rate of 5°C / min, calcined for 4 hours, ground and sieved to obtain composite carrier particles with a particle size of 3 mm, wherein the CeO2 loading in the composite carrier particles was 9%;

[0052] (3) The composite carrier particles were immersed in a mixed solution of equal volumes of chloroplatinic acid hexahydrate and palladium chloride, left at room temperature for 12 hours, then dried at 120°C for 6 hours, and then heated to 450°C at 5°C / min and calcined for 3 hours to obtain a catalyst for removing hydrocarbon impurities from carbon dioxide; wherein the loading amounts of platinum and palladium were 0.15% and 0.3%, respectively.

[0053] Comparative Example 2

[0054] A method for preparing a catalyst for removing hydrocarbon impurities from carbon dioxide comprises the following preparation steps:

[0055] (1) 6.58 parts by weight of tetraethyl orthosilicate was added to a mixed solvent of 18 parts by weight of deionized water and ethanol, and stirred at 300 rpm until aluminum chlorohydrate, tetraethyl orthosilicate, and magnesium chlorohydrate were completely dissolved, and the stirring was continued for 24 hours to fully hydrolyze the aluminum chlorohydrate, tetraethyl orthosilicate, and magnesium chlorohydrate to obtain a mixed solution; wherein the volume ratio of deionized water to ethanol in the mixed solvent of deionized water and ethanol was 1:1; 5.5 parts by weight of polyvinyl pyrrolidone as a coagulant aid was added dropwise to the mixed solution under stirring at 300 rpm, and the mixture was continued. Stir for 15 minutes, then transfer to a mold and let stand until a wet gel is formed, then age for 24 hours, then replace the excess water in the wet gel with 40°C anhydrous ethanol, and replace the ethanol every 12 hours for 7 days; place the replaced gel in a supercritical drying kettle, replace the oxygen in the kettle with nitrogen, and raise the pressure in the kettle to 2.5MPa, raise the temperature to 265°C, and control the pressure in the kettle to 7.5MPa at the same time, keep the pressure constant, keep the temperature constant for 1.5 hours, slowly release the pressure to normal pressure, and finally wait for the temperature to drop to room temperature to obtain a composite aerogel;

[0056] (2) The composite aerogel was immersed in an equal volume of cerium nitrate solution for 2 hours, dried naturally and then dried overnight, then heated to 550°C at a heating rate of 5°C / min, calcined for 4 hours, ground and sieved to obtain composite carrier particles with a particle size of 3 mm, wherein the CeO2 loading in the composite carrier particles was 9%;

[0057] (3) The composite carrier particles were immersed in a mixed solution of equal volumes of chloroplatinic acid hexahydrate and palladium chloride, left at room temperature for 12 hours, then dried at 120°C for 6 hours, and then heated to 450°C at 5°C / min and calcined for 3 hours to obtain a catalyst for removing hydrocarbon impurities from carbon dioxide; wherein the loading amounts of platinum and palladium were 0.15% and 0.3%, respectively.

[0058] Comparative Example 3

[0059] A method for preparing a catalyst for removing hydrocarbon impurities from carbon dioxide comprises the following preparation steps:

[0060] (1) 6.05 parts by weight of aluminum chlorohydrate and 2.35 parts by weight of tetraethyl orthosilicate are added to a mixed solvent of 18 parts by weight of deionized water and ethanol, and stirred at 300 rpm until the aluminum chlorohydrate, tetraethyl orthosilicate, and magnesium chlorohydrate are completely dissolved, and stirring is continued for 24 hours to fully hydrolyze the aluminum chlorohydrate, tetraethyl orthosilicate, and magnesium chlorohydrate to obtain a mixed solution; wherein the volume ratio of deionized water to ethanol in the mixed solvent of deionized water and ethanol is 1:1; 5.5 parts by weight of polyvinyl pyrrolidone, a coagulant aid, is added dropwise to the mixed solvent under stirring at 300 rpm. The mixture was stirred for 15 min, then transferred to a mold and allowed to stand until a wet gel was formed, and then aged for 24 h. The excess water in the wet gel was replaced with 40°C anhydrous ethanol, and the ethanol was replaced every 12 h for 7 days. The replaced gel was placed in a supercritical drying kettle, and the oxygen in the kettle was replaced with nitrogen. The pressure in the kettle was raised to 2.5 MPa, and the temperature was raised to 265°C. At the same time, the pressure in the kettle was controlled to 7.5 MPa, and the pressure was kept constant. After the temperature was kept constant for 1.5 h, the pressure was slowly released to normal pressure, and finally the temperature was lowered to room temperature to obtain a composite aerogel.

[0061] (2) The composite aerogel was immersed in an equal volume of cerium nitrate solution for 2 hours, dried naturally and then dried overnight, then heated to 550°C at a heating rate of 5°C / min, calcined for 4 hours, ground and sieved to obtain composite carrier particles with a particle size of 3 mm, wherein the CeO2 loading in the composite carrier particles was 9%;

[0062] (3) The composite carrier particles were immersed in a mixed solution of equal volumes of chloroplatinic acid hexahydrate and palladium chloride, left at room temperature for 12 hours, then dried at 120°C for 6 hours, and then heated to 450°C at 5°C / min and calcined for 3 hours to obtain a catalyst for removing hydrocarbon impurities from carbon dioxide; wherein the loading amounts of platinum and palladium were 0.15% and 0.3%, respectively.

[0063] Comparative Example 4

[0064] A method for preparing a catalyst for removing hydrocarbon impurities from carbon dioxide comprises the following preparation steps:

[0065] (1) 2.53 parts by mass of aluminum chlorohydrate and 3.91 parts by mass of magnesium chlorohydrate are added to a mixed solvent of 18 parts by mass of deionized water and ethanol, and stirred at 300 rpm until the aluminum chlorohydrate, ethyl orthosilicate, and magnesium chlorohydrate are completely dissolved, and stirring is continued for 24 hours to fully hydrolyze the aluminum chlorohydrate, ethyl orthosilicate, and magnesium chlorohydrate to obtain a mixed solution; wherein the volume ratio of deionized water to ethanol in the mixed solvent of deionized water and ethanol is 1:1; 5.5 parts by mass of polyvinyl pyrrolidone, a coagulant aid, is added dropwise to the mixture under stirring at 300 rpm; The mixed solution was stirred for 15 minutes, then transferred to a mold and allowed to stand until a wet gel was formed, and then aged for 24 hours. After that, the excess water in the wet gel was replaced with 40°C anhydrous ethanol, and the ethanol was replaced every 12 hours for 7 days. The replaced gel was placed in a supercritical drying kettle, and the oxygen in the kettle was replaced with nitrogen. The pressure in the kettle was raised to 2.5MPa, and the temperature was raised to 265°C. At the same time, the pressure in the kettle was controlled to 7.5MPa, and the pressure was kept constant. After the constant temperature was maintained for 1.5 hours, the pressure was slowly released to normal pressure, and finally the temperature was lowered to room temperature to obtain a composite aerogel.

[0066] (2) The composite aerogel was immersed in an equal volume of cerium nitrate solution for 2 hours, dried naturally and then dried overnight, then heated to 550°C at a heating rate of 5°C / min, calcined for 4 hours, ground and sieved to obtain composite carrier particles with a particle size of 3 mm, wherein the CeO2 loading in the composite carrier particles was 9%;

[0067] (3) The composite carrier particles were immersed in a mixed solution of equal volumes of chloroplatinic acid hexahydrate and palladium chloride, left at room temperature for 12 hours, then dried at 120°C for 6 hours, and then heated to 450°C at 5°C / min and calcined for 3 hours to obtain a catalyst for removing hydrocarbon impurities from carbon dioxide; wherein the loading amounts of platinum and palladium were 0.15% and 0.3%, respectively.

[0068] Comparative Example 5

[0069] A method for preparing a catalyst for removing hydrocarbon impurities from carbon dioxide comprises the following preparation steps:

[0070] (1) 1.316 parts by weight of tetraethyl orthosilicate and 5.18 parts by weight of magnesium chloride hexahydrate are added to a mixed solvent of 18 parts by weight of deionized water and ethanol, and stirred at 300 rpm until aluminum chloride hexahydrate, tetraethyl orthosilicate and magnesium chloride hexahydrate are completely dissolved, and stirring is continued for 24 hours to fully hydrolyze aluminum chloride hexahydrate, tetraethyl orthosilicate and magnesium chloride hexahydrate to obtain a mixed solution; wherein the volume ratio of deionized water to ethanol in the mixed solvent of deionized water and ethanol is 1:1; 5.5 parts by weight of polyvinyl pyrrolidone as a coagulant aid is added dropwise to the mixture under stirring at 300 rpm; The mixed solution was stirred for 15 minutes, then transferred to a mold and allowed to stand until a wet gel was formed, and then aged for 24 hours. After that, the excess water in the wet gel was replaced with 40°C anhydrous ethanol, and the ethanol was replaced every 12 hours for 7 days. The replaced gel was placed in a supercritical drying kettle, and the oxygen in the kettle was replaced with nitrogen. The pressure in the kettle was raised to 2.5MPa, and the temperature was raised to 265°C. At the same time, the pressure in the kettle was controlled to 7.5MPa, and the pressure was kept constant. After the constant temperature was maintained for 1.5 hours, the pressure was slowly released to normal pressure, and finally the temperature was lowered to room temperature to obtain a composite aerogel.

[0071] (2) The composite aerogel was immersed in an equal volume of cerium nitrate solution for 2 hours, dried naturally and then dried overnight, then heated to 550°C at a heating rate of 5°C / min, calcined for 4 hours, ground and sieved to obtain composite carrier particles with a particle size of 3 mm, wherein the CeO2 loading in the composite carrier particles was 9%;

[0072] (3) The composite carrier particles were immersed in a mixed solution of equal volumes of chloroplatinic acid hexahydrate and palladium chloride, left at room temperature for 12 hours, then dried at 120°C for 6 hours, and then heated to 450°C at 5°C / min and calcined for 3 hours to obtain a catalyst for removing hydrocarbon impurities from carbon dioxide; wherein the loading amounts of platinum and palladium were 0.15% and 0.3%, respectively.

[0073] Comparative Example 6

[0074] A method for preparing a catalyst for removing hydrocarbon impurities from carbon dioxide comprises the following preparation steps:

[0075] (1) 2.2 parts by mass of aluminum chlorohydrate, 0.94 parts by mass of tetraethyl orthosilicate, and 3.7 parts by mass of magnesium chlorohydrate are added to a mixed solvent of 18 parts by mass of deionized water and ethanol, and stirred at 300 rpm until the aluminum chlorohydrate, tetraethyl orthosilicate, and magnesium chlorohydrate are completely dissolved, and stirring is continued for 24 hours to fully hydrolyze the aluminum chlorohydrate, tetraethyl orthosilicate, and magnesium chlorohydrate to obtain a mixed solution; wherein the volume ratio of deionized water to ethanol in the mixed solvent of deionized water and ethanol is 1:1; 5.5 parts by mass of polyvinyl pyrrolidone, a coagulant aid, are taken and stirred at 300 rpm. The mixture was added dropwise to the mixed solution under the condition of 1% mol / l and stirred for 15 min. The mixture was then transferred to a mold and allowed to stand until a wet gel was formed. The mixture was then aged for 24 h. The excess water in the wet gel was replaced with anhydrous ethanol at 40 °C. The ethanol was replaced every 12 h for 7 days. The replaced gel was placed in a supercritical drying kettle. The oxygen in the kettle was replaced with nitrogen. The pressure in the kettle was raised to 2.5 MPa. The temperature was raised to 265 °C. The pressure in the kettle was controlled to 7.5 MPa. The pressure was kept constant. After the temperature was kept constant for 1.5 h, the pressure was slowly released to normal pressure. Finally, the temperature was lowered to room temperature to obtain a composite aerogel.

[0076] (3) The composite aerogel was immersed in a mixed solution of equal volumes of chloroplatinic acid hexahydrate and palladium chloride, left at room temperature for 12 h, then dried at 120°C for 6 h, then heated to 450°C at 5°C / min and calcined for 3 h to obtain a catalyst for removing hydrocarbon impurities from carbon dioxide; wherein the loading amounts of platinum and palladium were 0.15% and 0.3%, respectively.

[0077] Comparative Example 7

[0078] The catalyst for removing hydrocarbon impurities from carbon dioxide uses THC-2 dehydrogenation catalyst with a specific surface area of ​​140 to 250 m 2 / g, service life 1 to 3 years, the lowest full conversion temperature of methane is 350℃, and the strength is 32.6N / particle.

[0079] Effect example

[0080] In a fixed bed reactor, 30 mL of the catalyst for removing hydrocarbon impurities from carbon dioxide of the embodiment and comparative example was loaded, with a particle size of Φ3 mm. The feed gas was controlled by a mass flow meter with a space velocity of 1000 h -1 The composition of the raw gas is as follows: CH4 (0.5%), C6H6 (30×10 -6 ), O2 (1.2% to 1.4%), and the rest is CO2 balance gas; the raw gas and tail gas are analyzed by HP6890GC, the detector is FID, the chromatographic column is 5A molecular sieve, and high-purity nitrogen is used as the carrier gas; the minimum full conversion temperature of methane is tested, and the so-called minimum full conversion temperature of methane is to remove methane (0.5%) in the raw gas to ≤20×10 -6 The minimum temperature required.

[0081] Strength: The catalysts for removing hydrocarbon impurities from carbon dioxide of the examples and comparative examples were tested for crushing resistance according to HG / T 2782.

[0082] Table 1 shows the performance test results of the catalysts for removing hydrocarbon impurities from carbon dioxide prepared in the examples and comparative examples:

[0083] Table 1

[0084]

[0085]

[0086] From the comparison of the data of Example 2 and Comparative Examples 1 to 6 in Table 1, it can be seen that the catalyst for removing hydrocarbon impurities from carbon dioxide prepared in Example 2 has a large specific surface area, good low-temperature activity, a long service life, and good mechanical properties;

[0087] The main difference between Example 2 and Example 4 is the type of coagulant aid. Example 2 uses polyvinyl pyrrolidone, while Example 4 uses 1,2-propylene oxide. Polyvinyl pyrrolidone better regulates the gelation process and forms a more uniform and stable mesoporous structure, resulting in Example 2 having a higher specific surface area, a lower methane minimum full conversion temperature, and a longer service life.

[0088] The main difference between Example 2 and Comparative Example 1 is that Example 2 uses aluminum chlorohexahydrate, ethyl orthosilicate and magnesium chlorohexahydrate, while Comparative Example 1 only uses aluminum chlorohexahydrate; the catalyst of Example 2 has a larger specific surface area, better low-temperature activity, longer service life and better mechanical properties; The main difference between Example 2 and Comparative Example 2 is that Example 2 uses aluminum chlorohexahydrate, ethyl orthosilicate and magnesium chlorohexahydrate, while Comparative Example 2 lacks magnesium chlorohexahydrate. Example 2 has a larger specific surface area, better low-temperature activity, longer service life and better mechanical properties;

[0089] The main difference between Example 2 and Comparative Example 3 is that Example 2 uses aluminum chloride hexahydrate, tetraethyl orthosilicate and magnesium chloride hexahydrate, while Comparative Example 3 lacks magnesium chloride hexahydrate. Example 2 has a larger specific surface area, better low-temperature activity, longer service life and better mechanical properties.

[0090] The main difference between Example 2 and Comparative Example 4 is that Example 2 uses aluminum chlorohexahydrate, tetraethyl orthosilicate and magnesium chlorohexahydrate, while Comparative Example 4 lacks tetraethyl orthosilicate; Example 2 has a larger specific surface area, better low-temperature activity, longer service life and better mechanical properties;

[0091] The main difference between Example 2 and Comparative Example 5 is that Example 2 uses aluminum chlorohexahydrate, ethyl orthosilicate and magnesium chlorohexahydrate, while Comparative Example 5 lacks aluminum chlorohexahydrate; Example 2 has a larger specific surface area, better low-temperature activity, longer service life and better mechanical properties;

[0092] The main difference between Example 2 and Comparative Example 6 is the preparation step. Example 2 loads cerium oxide on the composite aerogel, while Comparative Example 6 does not have this step; Example 2 has a larger specific surface area, better low-temperature activity, longer service life, and better mechanical properties;

[0093] The main differences between Example 2 and Comparative Example 7 are the materials and preparation methods. Example 2 uses aluminum chlorohexahydrate, tetraethyl orthosilicate and magnesium chlorohexahydrate and is prepared by a sol-gel method, while Comparative Example 7 uses a commercial THC-2 dehydrogenation catalyst; Example 2 has a larger specific surface area, better low-temperature activity, longer service life, and better mechanical properties;

[0094] Example 2 uses a catalyst for removing hydrocarbon impurities from carbon dioxide. The sol-gel method is used to prepare aluminum chloride hexahydrate, tetraethyl orthosilicate, and magnesium chloride hexahydrate to obtain an aluminum oxide, silicon oxide, and magnesium oxide composite aerogel, which provides a high specific surface area and a rich pore structure, which is beneficial to the dispersion of active components and the transmission of reactants; the high specific surface area and pore structure of the composite aerogel in Example 2, as well as the oxygen storage capacity and high oxygen mobility of cerium oxide, significantly improve the low-temperature activity of the catalyst; the composite aerogel in Example 2 synergistically with cerium oxide has high mechanical strength and thermal stability, and cerium oxide has good thermal stability and dispersibility, which significantly extends the service life of the catalyst.

[0095] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A catalyst for removing hydrocarbon impurities from carbon dioxide, characterized in that: The catalyst for removing hydrocarbon impurities from carbon dioxide is prepared by loading active components on composite carrier particles; the composite carrier particles are prepared by loading a catalyst promoter, cerium oxide, on a composite aerogel and grinding and screening the composite aerogel; the composite aerogel is prepared by using a sol-gel method to prepare a coagulant and at least two aerogel precursors.

2. The catalyst for removing hydrocarbon impurities from carbon dioxide according to claim 1, characterized in that: The active components are palladium and platinum.

3. The catalyst for removing hydrocarbon impurities from carbon dioxide according to claim 1, characterized in that: The coagulant aid is 1,2-propylene oxide or polyvinyl pyrrolidone.

4. The catalyst for removing hydrocarbon impurities from carbon dioxide according to claim 1, characterized in that: The aerogel precursor adopts aluminum chloride hexahydrate, tetraethyl orthosilicate and magnesium chloride hexahydrate.

5. A method for preparing a catalyst for removing hydrocarbon impurities from carbon dioxide as claimed in any one of claims 1 to 4, characterized in that: The method comprises the following preparation steps: (1) preparing a composite aerogel by a sol-gel method using an aerogel precursor and a coagulant; (2) soaking the composite aerogel in a cerium nitrate solution, drying it naturally, calcining it, grinding it, and sieving it to obtain composite carrier particles; (3) The composite carrier particles are immersed in a mixed solution of active components, left to stand, dried, and calcined to obtain a catalyst for removing hydrocarbon impurities from carbon dioxide.

6. The method for preparing a catalyst for removing hydrocarbon impurities from carbon dioxide according to claim 5, characterized in that: The aerogel precursor adopts aluminum chloride hexahydrate, tetraethyl orthosilicate and magnesium chloride hexahydrate, and the mass fractions of aluminum chloride hexahydrate, tetraethyl orthosilicate and magnesium chloride hexahydrate are 2-2.4 mass parts, 0.94 mass parts and 3.5-3.9 mass parts respectively.

7. The method for preparing a catalyst for removing hydrocarbon impurities from carbon dioxide according to claim 5, characterized in that: The coagulant aid is polyvinyl pyrrolidone, and the mass fraction of polyvinyl pyrrolidone is 5.4 to 5.6 mass parts.

8. The method for preparing a catalyst for removing hydrocarbon impurities from carbon dioxide according to claim 5, characterized in that: The CeO2 loading amount of the composite carrier particles is 8-10%.

9. The method for preparing a catalyst for removing hydrocarbon impurities from carbon dioxide according to claim 5, characterized in that: The loading amount of the active component of the catalyst for removing hydrocarbon impurities from carbon dioxide is 0.45%.

10. The method for preparing a catalyst for removing hydrocarbon impurities from carbon dioxide according to claim 9, characterized in that: The active components are palladium and platinum, and the loading amounts of palladium and platinum on the catalyst for removing hydrocarbon impurities in carbon dioxide are 0.28-0.32% and 0.13-0.17% respectively.